2001
DOI: 10.1161/01.str.32.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Presentation and Evaluation for Acute Stroke

Abstract: Background and Purpose-Early treatment is a critical determinant of successful intervention in acute stroke. The study was designed to find current patterns of stroke care by determining delays in time from onset of signs or symptoms to arrival at the emergency department and to initial evaluation by physicians and by identifying factors associated with these delays. Methods-Data were prospectively collected by nurses and physicians from patients, patients' family members, and medical records from 10 hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
165
3
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(198 citation statements)
references
References 34 publications
21
165
3
3
Order By: Relevance
“…Elderly patients may have less understanding of the signs and symptoms of acute stroke than younger patients do, with greater comorbidity with chronic neurological disease like dementia, previous strokes, and progressive cardiac or pulmonary disease that might interfere with recognizing acute stroke (15,(17)(18)(19). By contrast, in the study by Lacy et al, patients over the age of 65 years arrived earlier than younger patients did (20). The date of occurrence was not different here, but some reports indicate higher incidence at nighttime (11,12,14).…”
Section: Discussionmentioning
confidence: 91%
“…Elderly patients may have less understanding of the signs and symptoms of acute stroke than younger patients do, with greater comorbidity with chronic neurological disease like dementia, previous strokes, and progressive cardiac or pulmonary disease that might interfere with recognizing acute stroke (15,(17)(18)(19). By contrast, in the study by Lacy et al, patients over the age of 65 years arrived earlier than younger patients did (20). The date of occurrence was not different here, but some reports indicate higher incidence at nighttime (11,12,14).…”
Section: Discussionmentioning
confidence: 91%
“…Paul, and Houston failed to show differences in delay to emergency department arrival for black patients 54, 55, 56, 57. More recent studies demonstrated significant differences in delay to arrival within 3 hours22, 52, 58 that persist after adjusting for age, sex, stroke severity, and insurance status 26. Boehme et al found that black women, specifically, are more likely to arrive outside of the 3‐hour time window than white men, black men, or white women 59.…”
Section: Discussionmentioning
confidence: 95%
“…Differences in time to presentation or utilization of EMS may also underlie differences in rt‐PA utilization 50, 51, 52, 53. Existing data on differences in prehospital delays and EMS use are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…22 In US stroke centers, up to 59% of the patients who presented within 24 hours of symptom onset arrived within 3 hours. [23][24][25] In countries such as the United Kingdom or Ireland, where tPA has not been approved for stroke treatment and systematic educational programs have not been performed, longer onsetto-arrival delays have been reported. 26 However, a third of the patients arrived within 3 hours and nearly half arrived within 6 hours of symptom onset.…”
Section: Discussionmentioning
confidence: 99%